Answer:
The equation of the normal line to the curve y = x² - 3x at the point (7, 28) is 11y + x - 315 = 0
Step-by-step explanation:
First, we need to find the slope of the line tangent to the curve at the point (7, 28).
To do this, we need to differentiate y with respect to x and evaluate at the point x0 = 7.
Given y = x² - 3x
dy/dx = 2x - 3
So, the slope, m of the tangent line is dy/dx at x = 7:
m = 2(7) - 3 = 11
Slope, m = 11
The slope, m2 of the line perpendicular to the tangent is given as m2 = -1/m
m2 = −1/11
Finally, given the slope m of a line, and a point (x0, y0) on the line, we can use the point-slope form of the equation of a line:
y - y0=m(x - x0)
The perpendicular line has slope m2 = -1/11, and (7, 28) is a point on that line, the desired equation is:
y - 28 = (-1/11)(x - 7)
Or multiplying by 11, we have
11y - 308 = -x + 7
11y + x - 315 = 0